Does Prejudice Mediate the Effect of Ethnocentrism on Discrimination? An Empirical Study on Interethnic Relations - Marselius Sampe Tondok; Dwiko Kusuma Indramawan; Ayuni Ayuni (ANIMA Indonesian Psychological Journal, 2017)
The purpose of this study was to examine whether prejudice was the mediator between ethnocentrism and interethnic discrimination. A survey was conducted at a university in Surabaya which has a multicultured student population (N = 300) recruited using incidental sampling. Data were collected using discrimination, ethnocentrism, and prejudice questionnaires. The hypothesis was tested using regression analysis with simple mediation. Results showed that prejudice was the mediator between ethnocentrism and discrimination (t = 12.637; p < .01); meanwhile ethnocentrism was not a predictor of discrimination when prejudice was controlled (t = 1.444; p > .05). Results also provide a suggestion to ethnic group members to be more open and control their prejudice toward other ethnic groups in order to grow positive inter-ethnic relationships.